Tocotrienol Supplementation Led to Higher Serum Levels of Lysophospholipids but Lower Acylcarnitines in Postmenopausal Women: A Randomized Double-Blinded Placebo-Controlled Clinical Trial - Shen, Chwan-Li; Mo, Huanbiao; Dunn, Dale M.; Watkins, Bruce A. (Frontiers in Nutrition, 2021)
Osteoporosis is a major health problem in postmenopausal women. Herein we evaluated the effects of 12-week tocotrienols (TT) supplementation on serum metabolites in postmenopausal, osteopenic women. Eighty-nine participants (59.76.8 yr, BMI 28.75.7 kg/m2) were assigned to 3 treatments: placebo (860 mg olive oil/day), 300mg TT (300 mg TT/day), and 600mg TT (600 mg TT/day) for 12 weeks. TT consisted of 90% -TT and 10% -TT. In this metabolomic study, we evaluated the placebo and 600mgTT at baseline and 12 weeks. As expected, TT and its metabolite levels were higher in the supplemented group after 12 weeks. At baseline, there were no differences in demographic parameters or comprehensive metabolic panels (CMP). Metabolomics analysis of serum samples revealed that 48 biochemicals were higher and 65 were lower in the 600mg TT group at 12 weeks, compared to baseline. The results confirmed higher serum levels of tocotrienols and lysophospholipids, but lower acylcarnitines and catabolites of tryptophan and steroids in subjects given 600mg TT. In summary, 12-week TT supplementation altered many serum metabolite levels in postmenopausal women. The present study supports our previous findings that TT supplementation helps reduce bone loss in postmenopausal osteopenic women by suppressing inflammation and oxidative stress. Furthermore, the body incorporates TT which restructures biomembranes and modifies phospholipid metabolism, a response potentially linked to reduced inflammation and oxidative stress.